The TOR-Auxin Connection Upstream of Root Hair Growth - Retzer, Katarzyna; Weckwerth, Wolfram (Plants (Basel, Switzerland), 2021)
Plant growth and productivity are orchestrated by a network of signaling cascades involved in balancing responses to perceived environmental changes with resource availability. Vascular plants are divided into the shoot, an aboveground organ where sugar is synthesized, and the underground located root. Continuous growth requires the generation of energy in the form of carbohydrates in the leaves upon photosynthesis and uptake of nutrients and water through root hairs. Root hair outgrowth depends on the overall condition of the plant and its energy level must be high enough to maintain root growth. TARGET OF RAPAMYCIN (TOR)-mediated signaling cascades serve as a hub to evaluate which resources are needed to respond to external stimuli and which are available to maintain proper plant adaptation. Root hair growth further requires appropriate distribution of the phytohormone auxin, which primes root hair cell fate and triggers root hair elongation. Auxin is transported in an active, directed manner by a plasma membrane located carrier. The auxin efflux carrier PIN-FORMED 2 is necessary to transport auxin to root hair cells, followed by subcellular rearrangements involved in root hair outgrowth. This review presents an overview of events upstream and downstream of PIN2 action, which are involved in root hair growth control.
Keywords: root growth; plant adaptation; auxin; ROS; ROP2; TOR signaling; PIN-FORMED 2; root hair growth; polar cell elongation